Peer Feedback to Stimulate Students’ Writing Process: A Case Study At a Vocational School in Ciamis - Ai Haiva Ingdriawati; Dedeh Rohayati (Universitas Galuh, 2023)
In the process of writing, the teacher always provides feedback to students even though it usually takes to do so. Thus, this study was designed to elaborate the use of peer feedback, the type of peer feedback, and students' perceptions of peer feedback to be compared with previous related research. The research site was at a Vocational High School in Ciamis. The data were gathered from observations and documents of students' writing. Then, the questionnaires were handed to 10 students who practice peer feedback in the writing class. The results showed that students used two types of feedback. They were direct feedback and indirect feedback. Furthermore, students' perceptions of peer feedback received a positive response and the most of students agreed that the implementation of peer feedback was more beneficial and it helped them improving their writing.